Increasing incidence of multidrug resistant Pseudomonas aeruginosa in inpatients of a tertiary care hospital - Prakash, Ved; Mishra, Prem Prakash; Premi, H. K.; Walia, Apoorva; Dhawan, Shikha; Kumar, Abhishek (International Journal of Research in Medical Sciences, 2017)
Background:Pseudomonas aeruginosa is an important pathogen isolated from various clinical infections. The occurrence of multidrug-resistant (MDR) Pseudomonas aeruginosa strains is increasing worldwide and limiting our therapeutic options resulting in high mortality. We aim to study the incidence of multidrug resistant Pseudomonas aeruginosa in inpatients from various departments along with rate of nosocomial infections. Methods:A cross sectional study from January 1, 2013 to December 31, 2013. A total of 167 Pseudomonas aeruginosa were isolated from 764 clinical specimens. The isolates were identified by standard microbiological techniques. The antibiotic susceptibility was done by Kirby Bauer method. Results:The highest number of isolates were from pulmonary samples n=90 (53.89%) followed by pus n=48 (28.74%). Overall, 39 (23.36%) isolates were nosocomial. The nosocomial isolates were mainly isolated from department of surgery, orthopaedics, obstetrics & gynaecology followed by others. Among 167 isolates screened, 53 (31.73%) were found to be MDR (resistant to ≥3 classes of antipseudomonal agents). The resistance was most against cephalosporins [Cefepime (65.26%), cefotaxime (60.47%)], fluoroquinolones [Ciprofloxacin (46.1%), levofloxacin (31.87%)] aminoglycosides [Amikacin (37.72%), gentamicin (31.13%)] followed by ureidopenicillins and carbepenems. About 56.75% isolates were suspected Metallo β lactamases producers. Conclusion:The study suggests that the incidence of nosocomial infection by multidrug resistant Pseudomonas aeruginosa is increasing globally especially the Metallo Beta lactamases producing strains. So there is a continuous need of conduction of surveillance programmes to formulate rational treatment strategies to combat this emerging challenge.